Permainan Tradisional sebagai Strategi Pembelajaran Penjas Berbasis Kearifan Lokal pada Mahasiswa PGSD - Marhani Marhani (Lembaga Yasin AlSys, 2026)
Although traditional games have been widely studied in the context of physical education in elementary schools, studies that specifically discuss their use in Physical Education learning among PGSD students remain limited. This study aims to analyze the relevance of traditional games as a Physical Education learning strategy in PGSD, particularly in developing motor skills, pedagogical competence, character values, and the preservation of local wisdom. This study used a qualitative approach with a structured literature review design. Data sources were obtained from curriculum documents, PJOK learning guidelines, physical activity recommendations, and scientific articles relevant to traditional games, physical education, and learning in elementary schools. Data were collected through documentation techniques and analyzed using content analysis by grouping the findings into the themes of curricular relevance, learning benefits, implementation strategies, and implementation challenges. The findings show that traditional games are relevant for use as a contextual, active, enjoyable, and culture-based Physical Education learning strategy. Traditional games support the development of locomotor, non-locomotor, and manipulative movements, coordination, balance, cooperation, sportsmanship, responsibility, and the ability of PGSD students to design PJOK learning that aligns with the characteristics of elementary school students. These findings contribute to the development of studies on physical education based on local wisdom and broaden understanding of the importance of integrating traditional games into the education of prospective elementary school teachers. The conclusion of the study affirms that traditional games play an important role in Physical Education learning in PGSD because they are able to connect aspects of movement, pedagogy, character, and culture. The implications of the study include theoretical contributions to the development of literature on Physical Education based on local culture, as well as practical implications for PGSD study programs, lecturers, and prospective teachers in designing PJOK learning that is contextual, inclusive, inexpensive, safe, and aligned with the needs of elementary school students.